Comparison of the efficacy of aflibercept and ranibizumab after a 3-month loading dose in patients with diabetic macular edema - Ekizoğlu, Ahmet; Çakmaklıoğulları, Murat (Journal of Surgery and Medicine, 2021)
Background/Aim: Diabetic macular edema (DME) is the main cause of visual loss in diabetic patients. Aflibercept and ranibizumab are among the most commonly used intravitreal agents in the DME. This study aims to compare the short-term anatomic and functional results of aflibercept and ranibizumab in the treatment of DME. Methods: This retrospective cohort study included newly diagnosed and treatment-naive DME patients. The patients were administered intravitreal aflibercept (IVA) or intravitreal ranibizumab (IVR) as a loading dose throughout 3 months. Pre-treatment and 1- and 3-month examinations were made of best corrected visual acuity (BCVA)and central macular thickness (CMT). After the treatment, the patients were classified in the 3rd month as those with good or poor response according to the early anatomic response. A good response to the treatment was considered the formation of foveal contour and full recovery of macular edema. Patients where macular edema was not fully resolved and/or foveal contour had not formed were classified as having poor response. Later, IVA and IVR were compared with each other in terms of response to treatment. Results: Evaluation was made of 67 eyes of 54 patients, comprising 31 (57.4%) females and 23 (42.6%) males with a mean age of 62.7 (7.3) years (range, 46-78 years). IVA was applied to 33 (49.3%) eyes and IVR to 34 (50.7%) eyes. In the IVA group, BCVA was determined as 0.75 (0.39) LogMAR pre-treatment, 0.53 (0.37) LogMAR at 1 month and 0.38 (0.30) LogMAR at 3 months (P<0.001 for each). CMT was measured as 400 (82) µm pre-treatment, 349 (95) µm at 1 month and 313 (79) µm at 3 months (P<0.001 for each). In the IVR group, BCVA was determined as 0.71 (0.34) LogMAR pre-treatment, 0.52 (0.34) LogMAR at 1 month and 0.39 (0.30) LogMAR at 3 months (P<0.001 for each). CMT was measured as 426 (92) µm pre-treatment, 365 (74) µm at 1 month and 323 (60) µm at 3 months (P<0.001 for each). A good response to treatment was determined in 24 eyes (72.7%) in the IVA group, and in 18 eyes (52.9%) in the IVR group. Although a good response to treatment was achieved at a higher rate in the IVA group, the difference was not statistically significant (P=0.09). Conclusion: Both visual and anatomic success was achieved with a 3-month loading dose in both the IVA and IVR groups. No statistically significant superiority was determined of one drug over the other in the 3-month period.